Classroom Management Skills Increase Interest and Learning Outcomes in Pancasila Education for Fourth Grade Elementary School Students - Putri, Tarissa Destriana; Astuti, Tri (Universitas Pendidikan Ganesha, 2024)
Students with more interest in learning often have low learning outcomes in learning activities. In order to achieve success in the learning process, teachers need to be able to manage the class effectively. Based on this, this research aims to analyze the influence of Class Management Skills on the Interest and Learning Outcomes of Class IV Elementary School Pancasila Education Students. This type of research is quantitative research. The research method used in the quantitative research design is the ex post facto method. The population in this study was all students in class IV elementary school, totaling 128 students. The sampling technique used in this research was purposive sampling. The methods used to collect data are interviews, questionnaires, and documentation. The instruments used to collect data were interviews, learning interests, and documentation. The data analysis technique used in this research is the inferential statistical analysis method using SPSS. The research results are that class management skills influence students' interest and learning outcomes in Pancasila education. It was concluded that Class Management Skills significantly increased student interest and learning outcomes in elementary schools.